Nightmares with the Bible: the good book and cinematic demons - Wiggins, Steve A. (Horror and scripture, 2020)
"Demons, as viewed through popular culture and history, are nightmares. This book considers demonic possession both historically and through the lenses of several popular movies that focus on exorcism"--